How Do We Go About Singing a New Song About Migration? - Caruso, Fulvia (European Journal of Musicology, 2022)
This article provides an overview of the questions that emerged from an action research project in the centre of the Padana Plain - Cremona Province and some surrounding provinces – in which the author, together with some students and former students, has been engaged since 2014. The aim of the still ongoing project is to understand the various levels of inclusion of migrants and asylum seekers in analysing their musical behaviours. The project is threefold: to document and analyse if and how the different migrant groups can  perform their rites; to organise musical workshops in middle schools in order, at the same time, to collect data about the musical listening and practices of children and to introduce them to transculturality through world and folk music; to organise musical workshops in Reception Centres for asylum seekers to understand if and how music has a role in their suspended lives and to try to use it for resilience. Considering that it is a right for migrants to be able to express their own culture and with the conviction that music is a strong tool in processes of dialogue and diversity acceptation, the project also envisages cultural events to create occasions of dialogue between the cultures that animate the area.